2020
DOI: 10.1038/s41419-020-03206-1
|View full text |Cite
|
Sign up to set email alerts
|

Concise review: current trends on applications of stem cells in diabetic nephropathy

Abstract: Diabetic nephropathy, with high prevalence, is the main cause of renal failure in diabetic patients. The strategies for treating DN are limited with not only high cost but an unsatisfied effect. Therefore, the effective treatment of DN needs to be explored urgently. In recent years, due to their self-renewal ability and multi-directional differentiation potential, stem cells have exerted therapeutic effects in many diseases, such as graft-versus-host disease, autoimmune diseases, pancreatic diseases, and even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 121 publications
0
5
0
Order By: Relevance
“…Stem cells can be classified according to their differentiation capability: (1) pluripotent stem cells; (2) multipotent stem cells; (3) unipotent stem cells ( 230 ). Mesenchymal stem cells (MSCs) are one of the most widely studied pluripotent stem cells in DN ( 231 ). Among these stem cells, MSCs have several advantages to apply in DN therapy, such as easy harvesting, multi-lineage differentiation potential, strong immunosuppression, and no immune rejection ( 232 ).…”
Section: Clinical and Pre-clinical Therapies Targeting The Immune Sys...mentioning
confidence: 99%
“…Stem cells can be classified according to their differentiation capability: (1) pluripotent stem cells; (2) multipotent stem cells; (3) unipotent stem cells ( 230 ). Mesenchymal stem cells (MSCs) are one of the most widely studied pluripotent stem cells in DN ( 231 ). Among these stem cells, MSCs have several advantages to apply in DN therapy, such as easy harvesting, multi-lineage differentiation potential, strong immunosuppression, and no immune rejection ( 232 ).…”
Section: Clinical and Pre-clinical Therapies Targeting The Immune Sys...mentioning
confidence: 99%
“…In addition, DN manifests itself as glomerular damage, glomerular hypertrophy, and thickening of the glomerular basement membrane. Patients who have DN typically have a poor renal prognosis since their condition is often misdiagnosed and difficult to treat ( 38 , 39 ). This may be one factor that contributes to the poor renal prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Corti et al unveiled the neuroprotective effect of bone marrow-derived c-kit + cells on degenerating motor neurons through anti-in ammatory function in a mouse model of amyotrophic lateral sclerosis [52]. It has been suggested that the trophic effect could be a major mechanism for the therapeutic properties of stem cell transplantation [53,54] by which stem cells promote cytoprotective, anti-in ammatory, and immune regulatory effects in a paracrine, endocrine, or autocrine manner and thus involved in improving diabetic nephropathy [55].…”
Section: Discussionmentioning
confidence: 99%